Knowing and unknowing transformative change: Epistemic inequities and epistemic justice in the IPBES transformative change assessment - Esther Turnhout; Peter Bridgewater; Josephine Chambers; Tim Forsyth; Qingxu Huang; Julia Leventon; Björn-Ola Linnér; Lyla Mehta; Valerie Nelson; Kristina Raab; Victoria Reyes-García; Catherine Sabinot; et al. (Environmental Science & Policy, 2026)

A meter-level resolution least-cost-path method for fast urban ventilation assessment: Preliminary validation using CFD and wind tunnel - Yueyang He; Kai Gao; Xinrui Guo; Man Kit Leung; Dicken Poon; Yuxiu Zu; Tim Huang; Kenneth Leung; Jenny Zhao; Kam Sing Wong; Chak Sang Yue; Yuk-ching Cheung; et al. (Building and Environment, 2026)

Building soil organic matter differing in physical fractions for fertilizer nitrogen retention - Quan Tang; Qingde Li; Xiaozhi Wang; Yuanyuan Huang; Tim J. Daniell; Enxuan Wu; Jing Wang; Feiyi Zhang; Zhenwang Li; Scott X. Chang; Zucong Cai; Yves Uwiragiye; et al. (Soil Biology and Biochemistry, 2026)

A network-based approach to understand the risk of mobility-related social exclusion in spatiotemporal activities - Zihan Kan; Jiaomin Wei; Tim Schwanen; Mei-Po Kwan; Dong Liu; Jianwei Huang (Journal of Transport Geography, 2026)

Neoarchean ultrahigh-temperature metamorphism in the Saglek–Hebron Complex, northern Labrador - Meiyun Huang; Shujuan Jiao; Tim E. Johnson; Jonathan O’Neil; Hanika Rizo; Chris Clark; Zhongwu Lan; Qiuli Li; Jinghui Guo (Precambrian Research, 2026)

Effect of slow food experience on WoM: The moderating role of food neophilia and the mediating role of eudaimonic and hedonic well-being - Mert Öğretmenoğlu; Gönül Akın; Ting-Yen Tim Huang; İsmail Kızılırmak (International Journal of Gastronomy and Food Science, 2026)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

Habitat quality outweighs the human footprint in driving spatial patterns of Cetartiodactyla in the Kunlun-Pamir Plateau - Xiaoran Huang; Yangfeng Wu; Anming Bao; Lei Zheng; Tao Yu; Sulei Naibi; Ting Wang; Fengjiao Song; Ye Yuan; Philippe De Maeyer; Tim Van de Voorde (Journal of Environmental Management, 2024)

A rapid procedure for isotopic purification of copper and nickel from seawater using an automated chromatography system - Xiaopeng Bian; Shun-Chung Yang; Robert J. Raad; Nicholas J. Hawco; Jude Sakowski; Kuo-Fang Huang; Kyeong Pil Kong; Tim M. Conway; Seth G. John (Analytica Chimica Acta, 2024)

Iron, Nickel, Copper, Zinc, and their stable isotopes along a salinity gradient in the Pearl River Estuary, southeastern China - Yaqing Ruan; Ruifeng Zhang; Shun-Chung Yang; Ziyuan Jiang; Sang Chen; Tim M. Conway; Kuo-Fang Huang; Edward A. Boyle; Meng Zhou; Seth G. John (Chemical Geology, 2024)

Cellular communication among smooth muscle cells: The role of membrane potential via connexins - Chun Xiao; Yishui Sun; Huaxiong Huang; Xingye Yue; Zilong Song; Tim David; Shixin Xu (Journal of Theoretical Biology, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Polymer elution and hydraulic conductivity of polymer-bentonite geosynthetic clay liners to bauxite liquors - Xing Chen; Yu Tan; Tim Copeland; Jiannan Chen; Daoping Peng; Tao Huang (Applied Clay Science, 2023)

The tempo of back-arc basin evolution: Insights from the early Paleozoic Proto-Tethyan North Qilian orogenic belt, northeastern Tibet - Dong Fu; Bo Huang; Simon A. Wilde; Tim E. Johnson; Ali Polat; Brian F. Windley; Zhaochu Hu; Zhipeng Zhou; Timothy M. Kusky (Earth and Planetary Science Letters, 2023)

Role of low-frequency wind variability in inducing WWBs during the onset of super El Niños - Yi-Kai Wu; Chi-Cherng Hong; Tim Li; An-Yi Huang (Climate Dynamics, 2023)

Brain Reactions to Opening and Closing the Eyes: Salivary Cortisol and Functional Connectivity - Shen-Da Chang; Po-Chih Kuo; Karl Zilles; Tim Q. Duong; Simon B. Eickhoff; Andrew C. W. Huang; Arthur C. Tsai; Philip E. Cheng; Michelle Liou (Brain Topography, 2022)
This study empirically assessed the strength and duration of short-term effects induced by brain reactions to closing/opening the eyes on a few well-known resting-state networks. We also examined the association between these reactions and subjects’ cortisol levels. A total of 55 young adults underwent 8-min resting-state fMRI (rs-fMRI) scans under 4-min eyes-closed and 4-min eyes-open conditions. Saliva samples were collected from 25 of the 55 subjects before and after the fMRI sessions and assayed for cortisol levels. Our empirical results indicate that when the subjects were relaxed with their eyes closed, the effect of opening the eyes on conventional resting-state networks (e.g., default-mode, frontal-parietal, and saliency networks) lasted for roughly 60-s, during which we observed a short-term increase in activity in rs-fMRI time courses. Moreover, brain reactions to opening the eyes had a pronounced effect on time courses in the temporo-parietal lobes and limbic structures, both of which presented a prolonged decrease in activity. After controlling for demographic factors, we observed a significantly positive correlation between pre-scan cortisol levels and connectivity in the limbic structures under both conditions. Under the eyes-closed condition, the temporo-parietal lobes presented significant connectivity to limbic structures and a significantly positive correlation with pre-scan cortisol levels. Future research on rs-fMRI could consider the eyes-closed condition when probing resting-state connectivity and its neuroendocrine correlates, such as cortisol levels. It also appears that abrupt instructions to open the eyes while the subject is resting quietly with eyes closed could be used to probe brain reactivity to aversive stimuli in the ventral hippocampus and other limbic structures.

Why SST trend in North Pacific is peculiarly negative against warming trend elsewhere since 1958 - Yu Huang; Tim Li; Bo Wu (Climate Dynamics, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

East Asian climate under global warming: understanding and projection - Jianping Li; Huang-Hsiung Hsu; Wei-Chyung Wang; Kyung-Ja Ha; Tim Li; Akio Kitoh (Climate Dynamics, 2018)

Divergent El Niño responses to volcanic eruptions at different latitudes over the past millennium - Fei Liu; Jinbao Li; Bin Wang; Jian Liu; Tim Li; Gang Huang; Zhiyuan Wang (Climate Dynamics, 2018)

Fecal microbiota of lambs fed purple prairie clover (Dalea purpurea Vent.) and alfalfa (Medicago sativa) - Qianqian Huang; Devin B. Holman; Trevor Alexander; Tianming Hu; Long Jin; Zhongjun Xu; Tim A. McAllister; Surya Acharya; Guoqi Zhao; Yuxi Wang (Archives of Microbiology, 2018)

Use of stable isotopes to understand food webs in Macao wetlands - Qian Chen; Yang Liu; Wei-Tim Ho; Shek Kiu Chan; Qiu-hua Li; Jian-Rong Huang (Wetlands Ecology and Management, 2017)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

ENSO-phase dependent TD and MRG wave activity in the western North Pacific - Liang Wu; Zhiping Wen; Tim Li; Ronghui Huang (Climate Dynamics, 2014)

The intraseasonal oscillations of precipitation and circulations from January to March in 2010 in East Asia - Suxiang Yao; Qian Huang; Tim Li; Chunying Zhang (Meteorology and Atmospheric Physics, 2014)

Environmental justice of nuclear waste policy in Taiwan: Taipower, government, and local community - Gillan Chi-Lun Huang; Tim Gray; Derek Bell (Environment, Development and Sustainability, 2013)

Synthesis, characterization, and biological studies of emissive rhenium–glutamine conjugates - Rachel Huang; Graeme Langille; Ravanjir K. Gill; Cindy Mei Jin Li; Yuji Mikata; May Q. Wong; Donald T. Yapp; Tim Storr (JBIC Journal of Biological Inorganic Chemistry, 2013)

Cannabidiol potentiates Δ9-tetrahydrocannabinol (THC) behavioural effects and alters THC pharmacokinetics during acute and chronic treatment in adolescent rats - Charlotte Klein; Emily Karanges; Adena Spiro; Alexander Wong; Jarrah Spencer; Thanh Huynh; Nathan Gunasekaran; Tim Karl; Leonora E. Long; Xu-Feng Huang; Kelly Liu; Jonathon C. Arnold; et al. (Psychopharmacology, 2011)

Protein profile analysis of salt-responsive proteins in leaves and roots in two cultivars of creeping bentgrass differing in salinity tolerance - Chenping Xu; Tim Sibicky; Bingru Huang (Plant Cell Reports, 2010)

Immunogenicity and efficacy of a bacterially expressed HEV ORF3 peptide, assessed by experimental infection of primates - Hongxia Ma; Xiaoguo Song; Tim J. Harrison; Rongcheng Li; Guoyong Huang; Heqiu Zhang; Wei Kong; Youchun Wang (Archives of Virology, 2009)

Quantitative assessment of DNA methylation: potential applications for disease diagnosis, classification, and prognosis in clinical settings - Romulo Martin Brena; Tim Hui-Ming Huang; Christoph Plass (Journal of Molecular Medicine, 2006)

Association of ErbB2 Ser1113 phosphorylation with epidermal growth factor receptor co-expression and poor prognosis in human breast cancer - Xiaomei Ouyang; Tim Gulliford; Hongyi Zhang; Gillian Smith; Guocai Huang; Richard J. Epstein (Molecular and Cellular Biochemistry, 2001)